Amplifying the response of soft actuators by harnessing snap-through instabilities - Overvelde, Johannes T B; Kloek, Tamara; D'haen, Jonas J A; Bertoldi, Katia (Proceedings of the National Academy of Sciences - PNAS, 2015)
Soft, inflatable segments are the active elements responsible for the actuation of soft machines and robots. Although current designs of fluidic actuators achieve motion with large amplitudes, they require large amounts of supplied volume, limiting their speed and compactness. To circumvent these limitations, here we embrace instabilities and show that they can be exploited to amplify the response of the system. By combining experimental and numerical tools we design and construct fluidic actuators in which snap-through instabilities are harnessed to generate large motion, high forces, and fast actuation at constant volume. Our study opens avenues for the design of the next generation of soft actuators and robots in which small amounts of volume are sufficient to achieve significant ranges of motion.